101 The importance of the multidisciplinary team (MDT) in the management of patients with multiple sclerosis. Issue 6 (27th May 2022) - Ramsay, Stephen; Spence, Robert; Robinson, Rebecca; Bhattacharya, Debarata; Nelson, Adam; Flynn, Peter; Droogan, Aidan; Hughes, Stella; Kennedy, Fiona; McDonnell, Gavin
Abstract : Background: Clinical decision-making for patients with MS relies heavily on the expertise of radiologists. In June 2018 we developed a monthly MDT meeting with neuroradiology to review complex cases. In this study, we assess the rate and clinical significance of variance between original MRI reports and those following MDT review. Methods: A 6-month retrospective study was performed. Data focused on the frequency of scan report revisions and subsequent impact on clinical management. Results: We analysed 157 cases. Of these, 68% had confirmed MS whilst 32% were under investigation. Of the 157, 64% were originally reported by a general radiologist and 36% by neuroradiology. Following neuroradiology review, 63 cases (40%) had the original report amended; of these, 81% were originally authored by a non-neuroradiologist. MDT review amended 64% of original reports from general radiology. The most frequently occurring revision was identification of additional, originally unreported inflammatory lesions. Of the 63 report revisions, 29% resulted in a change in clinical management. Overall, 4% of patients with a diagnosis of MS had this diagnosis questioned or reversed following MDT review of their imaging. Conclusions: This study demonstrates a high rate of variance in MRI reporting between general and neuroradiologists. This has clear implications for patient management, confirming the importance of dedicated MDTs involving specialist neuroradiology. sramsay03@qub.ac.uk|ABN Bursary